Microvascular Decompression for Trigeminal Neuralgia Caused by Venous Offending on the Ventral Side of the Root Entrance/Exit Zone: Classification and Management Strategy - Wang, Wenhua; Yu, Feng; Kwok, Sze Chai; Wang, Yuhai; Yin, Jia (Frontiers in Neurology, 2022)
Background Trigeminal neuralgia (TGN) is typically caused by an offending artery (OA) but may also involve an offending vein. Venous offending on the ventral side of the root entrance/exit zone (VO-VREZ) is particularly challenging. Objective To analyze the rate and pattern of VO-VREZ and propose management strategy accordingly. Methods VO-VREZ was classified into 3 types based on its anatomical relationship with a nerve root (A, the vein was covered by the nerve root entirely; B, the vein was lateral to the nerve root; and C, the vein penetrated the nerve root) and 3 groups based on the absence/presence of offending artery (I, no OA; II, suspected OA; and III, definitive OA). Results The analysis included 143 cases with complete follow-up. Type A, B, and C accounted for 11.9, 31.5, and 56.6% of the cases, respectively. Group I, II, and III accounted for 24.5, 26.6, and 49.0%, respectively. Most group I VO-VREZ cases (26 out of 31) were managed with coagulation followed by division. Most group II VO-VREZ cases (31 out of 38) were decompressed with shredded Teflon interposition. Group III VO-VREZ was left in place in all 70 cases. Immediate pain relief was achieved in all cases. Temporary hemifacial hypesthesia occurred in 21 patients (14.7%), among which 14 were managed with Teflon decompression. Within the 4.5-year median follow-up, pain recurred in 11 patients (7.7%), but all with lesser intensity. Conclusion VO-VREZ is not uncommon in patients with TGN. Different management strategy should be chosen according to the anatomical feature and the absence/presence of arterial conflict.